Performance implications of using signaling and screening for expanding interfirm business networks: evidence from franchising - Sadeh, Farhad; Kacker, Manish; Michael Lee-Chin & Family Institute for Strategic Business Studies (My University, 2020)
Entrepreneurial business firms such as franchisors can enhance their network performance by attracting high-quality partners and preventing low-quality partners from joining the network.We draw on agency and transaction cost theories and the substantive literature on voluntary information disclosure to develop a theoretical framework that examines the consequences of using signaling and screening mechanisms for interfirm network performance.Our model posits a complementary effect for signaling and screening because of their ability to offset the disadvantages of each other. We empirically evaluate our hypotheses through econometric analyses of a unique multi-sector panel dataset from the U.S. franchising industry. We find that ex-ante signaling and screening at the contractual relationship formation stage are complementary mechanisms that enhance network performance when they are used together. Additionally, we find that specific investments by the focal firm and by the partners positively moderate the performance impact of screening and signaling,respectively. Our findings suggest that the joint use of screening and signaling and the synchronization of specific investment commitments by both sides can assist an entrepreneurial business network in mitigating the double-sided adverse selection problem at the formation stage of dyadic network partnerships and enhancing network performance. Valuation Insight: The paper shows how franchisors can use a combination of screening and signaling mechanisms to add value to their firm by improving the quality of partners they attract to their network.
43 p. ; Includes bibliographical references (pp. 33-38) ; Authors "thank three anonymous reviewers, Josef Windsperger, William Allender, Kersi Antia, Charles Ingene, Robert Palmatier, Sourav Ray and Ruhai Wu for their constructive comments on previous versions of this paper. This paper has benefited from feedback received during presentations at the 2018 EMNet conference, the 2017 ISOF conference, the 2017 ETSymposium on Marketing Strategy, the ASAC 2017 conference, the 2018 Winter AMA conference, and research seminars at McMaster University, Indian Institute of Management (Bangalore) and Indian Institute of Management (Ahmedabad). This research is supportedby funding from the Social Sciences and Humanities Research Council of Canada. Funding for this research was provided by the Institute for the Study of Business Markets of the Pennsylvania State University."
Keywords: Business network; Signaling; Screening; Sales performance; Double-sided adverse selection; Interfirm relationships; Franchising; Voluntary information disclosure; Panel data analyses